2007
DOI: 10.3354/cr00722
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of spring arrival dates differ in two hirundines

Abstract: We examined the first arrival dates in the UK over a 56 yr period of 2 hirundines, sand martin Riparia riparia and barn swallow Hirundo rustica, in relation to temperatures along migration routes and at destination. Changes in arrival dates have been much greater for sand martin than for barn swallow, and the arrival order of the 2 species now appears to have reversed. There appear to be 2 reasons for this: a greater response to temperatures in SW Europe and a different response to temperature in recent years,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 22 publications
3
36
0
1
Order By: Relevance
“…Gauteng is the northernmost South African province we examined and the one for which we had the most data. In this region, barn swallows advanced their departure by a similar amount to their earlier arrival in Europe (4 -8 days) [4,20].…”
Section: Discussionmentioning
confidence: 98%
“…Gauteng is the northernmost South African province we examined and the one for which we had the most data. In this region, barn swallows advanced their departure by a similar amount to their earlier arrival in Europe (4 -8 days) [4,20].…”
Section: Discussionmentioning
confidence: 98%
“…Increasing migration speed under high temperatures (Cochran & Wikelski 2005, Marra et al 2005, Saino et al 2007, Sparks & Tryjanowksi 2007 may seem an important adaptation to track climatic variability, because it allows birds to arrive and breed earlier in warm years. However, if the temperatures en route do not have high predictive power for the circumstances at the breeding grounds, this strategy fails, and may even lead to individuals arriving too early if they do not halt their migration when encountering adverse circumstances (Brown & Brown 1998).…”
Section: Temperatures Trends During Migrationmentioning
confidence: 99%
“…It is unclear why, so far, no reports exist of evolutionary responses in laying dates, because selection for early laying has increased in several species (Visser et al 1998, Both & Visser 2001; but see Reale et al 2003). Although several studies have shown that spring migration dates are also related to environmental variables at the wintering grounds or en route (Huin & Sparks 1998, Coppack & Both 2002, Ahola et al 2004, Bairlein & Hüppop 2004, Saino et al 2004, 2007, Both et al 2005, Gordo & Sanz 2006, Hüppop & Winkel 2006, Sparks & Tryjanowksi 2007, changes in spring migration have recently been claimed to be an evolutionary response to climate change (Jonzén et al 2006). This reasoning was based on the fact that many migrants have advanced their passage through the Mediterranean (measured at an Italian study site) during the last decades, and that ecological circumstances south of this area had not improved.…”
Section: Evolution Of Migration and Breeding Datesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, this study provides a great opportunity to test co-fluctuations between morphologically and habitatsimilar bird species. If conditions on wintering grounds are important (as we assume, see above and [1,4,5]), and provide a clear environmental signal to commence migration from Africa to their breeding grounds, the warblers should show similar arrival patterns [12, but see also 13].…”
Section: Introductionmentioning
confidence: 99%